Effect of optimized germination technology on polyphenol content and hypoglycemic activity of mung bean - Li, Bo; Shen, Xinting; Shen, Huifang; Zhou, Ye; Yao, Xinmiao (Frontiers in Nutrition, 2023)
The study aimed to investigate the effect of germination conditions on the content of polyphenol extract in mung bean and to further investigate the effect of polyphenol extract in germinated mung bean on diabetic mice. Through single factor experiment and response surface experiment, the effects of soaking temperature, soaking time, germination temperature, germination time and soaking liquid CaCl2 concentration on the polyphenol content of mung bean were analyzed. The optimal germination conditions of mung bean were determined as soaking temperature 25℃, soaking time 11 h, germination temperature 28℃, germination time 3 d and CaCl2 concentration 2 mM. Under these conditions, the content of polyphenol extract in germinated mung bean was 4.878±0.30 mg/g, which was 3.07 times higher than that in ungerminated mung bean. The structure and content of purified polyphenols in germinated mung bean were determined by HPLC-MS/MS. Quinic acid, Quercetin, Rutin, Vitexin, Isovitexin and other substances were identified, and the content of polyphenols was 65.19%. In addition, through the in vivo and in vitro hypoglycemic activity experimental study of germinated mungbean polyphenols extract, the results showed that germinated mungbean polyphenols had an in vitro inhibitory effect on α-glucosidase, IC50 was 44.45 mg/mL. In vitro inhibitory activity was stronger after digestion. Polyphenol extract can significantly reduce blood sugar and improve insulin resistance in Type 2 diabetic mice(T2DM). According to the results, germination treatment is an effective way to increase the content of polyphenols in mung bean, and the polyphenols extract has hypoglycemic activity.